Effekte eines Interventionsprogramms zur Förderung der sozialen Partizipation auf die Einstellungen von Grundschulkindern gegenüber Peers mit sonderpädagogischem Förderbedarf. Vortrag auf der 10. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: „Bildung zwischen Unsicherheit und Evidenz“. - Löper, Marwin Felix; Görel, Gamze; Hellmich, Frank

Consistent Optical and Electrical Noise Figure - Noé, Reinhold (Journal of Lightwave Technology)

Tschirk, Wolfgang. "Vom Universum des Denkens. Eine Geistesgeschichte der Logik". Springer: Berlin 2022, xvii, 117 S. - Peckhaus , Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Boron‐Centered Lewis Superacid through Redox‐Active Ligands: Application in C–F and S–F Bond Activation - Köring, Laura; Stepen, Arne; Birenheide, Bernhard; Barth, Simon; Leskov, Maxim; Schoch, Roland; Krämer, Felix; Breher, Frank; Paradies, Jan (Angewandte Chemie International Edition)
Keywords: General Chemistry; Catalysis

Frustrated Lewis Pair Catalysed Reactions - Zhou, Rundong; Tavandashti, Zoleykha; Paradies, Jan (SynOpen)
In recent years, frustrated Lewis pairs have been widely used in small molecules activation and catalytic transformations. This graphic review is aimed to provide the fundamental understanding of frustrated Lewis pair reactivity and the exploitation thereof in catalytic reactions.
Keywords: Organic Chemistry; Materials Science (miscellaneous); Biomaterials; Catalysis

The association of chronotype and social jet lag with body composition in German students: The role of physical activity behaviour and the impact of the pandemic lockdown - Krueger, Betina; Stutz, Bianca; Jankovic, Nicole; Alexy, Ute; Kilanowski, Anna; Libuda, Lars; Buyken, Anette E. (PLOS ONE)
Young adults with a later chronotype are vulnerable for a discrepancy in sleep rhythm between work- and free days, called social jet lag (SJL). This study analysed (i) chronotype/SJL association with visceral fat/skeletal muscle mass, (ii) the attribution to physical activity behaviour, and (iii) chronotype-specific changes in physical activity behaviour in young adults during the Covid-19 pandemic lockdown. Chronotype and SJL were derived from the Munich-Chrono-Type-Questionnaire in 320 German students (age 18–25 years) from September 2019 to January 2020, 156 of these participated in an online follow-up survey in June 2020. Body composition was assessed by bioimpedance analysis at baseline. Multivariable linear regression analyses were used to relate chronotype/SJL to body composition; the contribution of self-reported physical activity was tested by mediation analysis. At baseline, a later chronotype and a larger SJL were associated with a higher visceral fat mass (P<0.05), this relation was notably mediated by the attention to physical activity (P<0.05). Chronotype (P = 0.02) but not SJL (P = 0.87) was inversely associated with skeletal muscle mass. During the pandemic lockdown, chronotype hardly changed, but SJL was reduced. Timing and physical activity behaviour remained in most participants and changes were unrelated to chronotype (all P>0.07). A later chronotype/higher SJL may increase the risk of a higher visceral fat mass even in this relatively healthy sample, which may be partly due to their physical activity behaviour. Despite a reduction in SJL during the pandemic lockdown, later chronotypes did not change their physical activity behaviour more than earlier chronotypes.
Keywords: Multidisciplinary

Politisch-humanistische Positionen in Reisenarrativen über Frankreich der 1920er und 1930er Jahre:„La lumière“ – Joseph Roths poetischer und medienreflexiver Humanismus - Öhlschläger, Claudia (Narrative des Humanismus in der Weimarer Republik und im Exil. Zur Aktualität einer kulturpolitischen Herausforderung für Europa.)

Die Schrift entHeiligen. Praktisch-theologische Überlegungen zum Bibelgebrauch als Transformation des Heiligen - Schroeter-Wittke, Harald (Heilige Schriften in der Kritik. XVII. Europäischer Kongress für Theologie (5.-8. September 2021 in Zürich). VWGTh 68)

Ostermontag (10.04.2023) Lk 24,13-35: Ostern to go! Oder: Wie Religionspädagogik geht - Schroeter-Wittke, Harald (Göttinger Predigtmeditationen)

Schule und Schulträger im Dialog: Gelingensbedingungen von Runden Tischen zur gemeinsamen Gestaltung des Digitalisierungsprozesses - Hagemann, L.; Herzig, Bardo; Möller-Glesemann, B. (Schulwelt NRW)

Updatable Privacy-Preserving Reputation System based on Blockchain - Pilot, Matthias

Epistemic Programming - Hüsing, Sven; Schulte, Carsten; Winkelnkemper, Felix (Computer Science Education)

Lehre in Zeiten von Digitalisierung und Inklusion – Beispiele aus drei Fächern. - Schmidt, Rebekka; Tenberge, Claudia; Häsel-Weide, Uta

Gathering a Euclidean Closed Chain of Robots in Linear Time and Improved Algorithms for Chain-Formation - Castenow, Jannik; Harbig, Jonas; Jung, Daniel; Knollmann, Till; Meyer auf der Heide, Friedhelm (Theoretical Computer Science)
Keywords: General Computer Science; Theoretical Computer Science

Distortional effects of separate accounting and formula apportionment on factor allocation - Ortmann, Regina; Pummerer, Erich (Journal of Business Economics)
Abstract We examine distortions caused by tax base allocation systems–separate accounting (SA) or formula apportionment (FA)–with respect to the allocation of assets and workforce within multinational entities (MNEs). The effects of both systems are intensively debated by EU Member States as they are striving to implement a European tax system. Its introduction would lead to a switch from SA to FA. Moreover, Pillar One of the recent global tax reform includes a mix of both tax base allocation systems. We find that, against the claims of the EU, FA does not necessarily create lower distortions of the factor allocation. Decisive for that assessment is the level of profit shifting under SA. Our results indicate that, in tendency, the factor allocation is more severely distorted by FA when the profit shifting possibilities were rather low under SA. In contrast to former studies, we highlight the importance of analyzing the status quo under the recently applied system (SA) in order to be able to assess the consequences of a switch from SA to FA. Our results are interesting for policy-makers as they help anticipating reactions of MNEs to a change in the applied tax base allocation system and for companies as a basis for future tax planning.
Keywords: Economics and Econometrics; Business and International Management

Die mündliche Prüfung. Eine Einführung - Matz, Frauke; Rogge, Michael; Rumlich, Dominik

Mechatronik und elektrische Antriebe / Mechatronics and electrical drives - Böcker, Joachim

Reusability of Germany´s total diet study food list upon availability of new food consumption data—comparison of three update strategies - Kolbaum, Anna Elena; Ptok, Sebastian; Jung, Christian; Libuda, Lars; Lindtner, Oliver (Journal of Exposure Science & Environmental Epidemiology)
Abstract Background The German total diet study (TDS)—BfR MEAL Study—established its food list in 2016 based on food consumption data of children (0.5–<5 years) and adults (14–80 years). The list consists of 356 foods selected for analysis in order to ensure ≥90% coverage of the diet. Recently, new food consumption data for children (0.5–<6 and 6–<12 years) in Germany became available, which raised the opportunity to evaluate the applicability of the MEAL food list 2016 on new data. Objective We tested the hypotheses that the MEAL food list 2016 also covers ≥90% of the diet of the new collected food consumption data, and that the selection of foods from younger children and adults was sufficient to also cover the middle age group (6–<12 years). Strategies for updating the existing food list were assessed. Methods Three approaches evaluated the reusability and potential adjustment strategies of the existing food list. Approach 1 applied the existing food list to new food consumption data. Approach 2 allowed the extension of the existing food list to improve coverage of food consumption. Approach 3 set up a new food list based on the new data. Results The MEAL food list 2016 covered 94% of the overall diet of the new collected food consumption data. The diet of the middle age group was sufficiently covered with 91%. However, coverage on main food group or population subgroup level was <90% in some cases. Approach 3 most accurately identified relevant modifications to the existing food list. 94% of the MEAL food list 2016 could be re-used and 51 new foods were identified as potentially relevant. Significance The results suggest that a high investment in the coverage of a TDS food list will lower the effort and the resources to keep data updated in the long-term. Impact There is no established approach to update a TDS food list. This study provides comparative approaches to handle newly collected food consumption data for follow-on TDS activities. The results provide useful information for institutions planning or updating a TDS. Furthermore, new food consumption data for children in Germany recently became available and are here presented for the first time.
Keywords: Public Health; Environmental and Occupational Health; Pollution; Toxicology; Epidemiology

Enhancing Comprehension and Navigation in Jupyter Notebooks with Static Analysis - Shivarpatna Venkatesh, Ashwin Prasad; Wang, Jiawei; Li, Li; Bodden, Eric (IEEE International Conference on Software Analysis, Evolution and Reengineering (SANER))

Immaterielles Kulturerbe in Nordrhein-Westfalen. Zur Bedeutung kultureller Ausdrucksformen - Harnack, Maria (Immaterielles Kulturerbe und regionale Identität – Schützenwesen in Deutschland)